Atomic‐Level Platinum Filling into Ni‐Vacancies of Dual‐Deficient NiO for Boosting Electrocatalytic Hydrogen Evolution (Adv. Energy Mater. 24/2022). Issue 24 (23rd June 2022) - Yan, Yaotian; Lin, Jinghuang; Xu, Tianxiong; Liu, Baishen; Huang, Keke; Qiao, Liang; Liu, Shude; Cao, Jian; Jun, Seong Chan; Yamauchi, Yusuke; Qi, Junlei
Abstract : Hydrogen Evolution Reaction In article number 2200434, Shude Liu, Yusuke Yamauchi, Junlei Qi and co‐workers propose a vacancy‐driven strategy for filling Pt into Ni‐vacancies to boost hydrogen evolution reaction activity. The Pt atoms filling into the Ni vacancies subsequently combine with additional O vacancies to tune the electronic structure of surrounding Ni sites, leading to a superior mass activity.